2011
DOI: 10.1097/tp.0b013e3181fd0179
|View full text |Cite
|
Sign up to set email alerts
|

Increased Early Graft Failure in Right-Sided Living Donor Nephrectomy

Abstract: Right-sided donor nephrectomy is associated with a small increased risk of allograft failure regardless of open or laparoscopic approach. However, the low observed risk of allograft failure with right-sided nephrectomy suggests that recovering the right kidney is a reasonable option for donors with contraindications for donating the left kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
2
29
1
1
Order By: Relevance
“…We considered that the more complex anatomic structures surrounding the left kidney may cause some but not serious intraoperative effects on the operation because the longer renal vein of the left side may make the implant procedure less demanding and may reduce the difficulty of the operation. [21][22][23] Therefore, in our analysis, the right side did not have an advantage regarding the rate of overall donor intraoperative complications compared with the left side. For urologists, early recovery of graft function is most concerning.…”
Section: Discussionmentioning
confidence: 88%
“…We considered that the more complex anatomic structures surrounding the left kidney may cause some but not serious intraoperative effects on the operation because the longer renal vein of the left side may make the implant procedure less demanding and may reduce the difficulty of the operation. [21][22][23] Therefore, in our analysis, the right side did not have an advantage regarding the rate of overall donor intraoperative complications compared with the left side. For urologists, early recovery of graft function is most concerning.…”
Section: Discussionmentioning
confidence: 88%
“…We defined EGF as graft failure within 90 days after transplantation, in accordance with previous studies. 14 …”
Section: Study Population and Designmentioning
confidence: 97%
“…2,4,[8][9][10][11][12][13] However, a recent multi-institutional large cohort study found that the early graft failure (EGF) rate (within 90 days) of right LLDN was higher than the EGF rate of left LLDN. 14 In addition, right OLDN allografts had higher EGF rates than left OLDN allografts. 14 However, all these studies were relatively short-term investigations, and no data have been reported regarding the long-term survival rate of left vs right allografts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diese Ergebnisse widersprechen den Daten von Hsu et al, die ein erhöhtes Risiko für ein Transplantatversagen bei rechtseitiger Spendernephrektomie sowohl bei der konventionellen als auch bei der laparoskopischen Entnahmetechnik nachweisen konnten [26].…”
Section: Diskussionunclassified